Effect of Zam Zam water and plant extracts on germination and seedling growth of Hibiscus esculentus and effect upon growth of Rhizoctonia solani - Wafik A. Al-kaisi (Journal of Madenat Alelem University College, 2011)
The research was conducted to study the effect of Zamzam water and leaves extract of Salvia sclarea, Rosmarinus officinalis and Thymus vulgaris with 10% and 20% concentration on germination of seeds and growth of seedling of Hibiscus esculentus. The effect of treatments on infection percentage seed decay, and surface growth of Rhizoctonia solani and analysis of the extracts using High Performance Liquid Chromatography (HPLC) were studied. The results showed that all treatments effected significantly in percentage of seeds germination, acceleration of germination, promoter indicator, speed elongation of radical and plumule, the infection percentage of seeds decay and surface growth of R. solani was reduced. The research was conducted to detect the active compounds in extract of plants using (HPLC).